1994
DOI: 10.1073/pnas.91.22.10610
|View full text |Cite
|
Sign up to set email alerts
|

11q23 translocations split the "AT-hook" cruciform DNA-binding region and the transcriptional repression domain from the activation domain of the mixed-lineage leukemia (MLL) gene.

Abstract: Translocations involving chromosome band 11q23, found in acute lymphoid and myeloid leukemia, disrupt the MLL gene. This gene encodes a putative transcription factor with homology to the zinc fingers and other domains of the Drosophila trithorax gene product and to the "AT-hook" motif of hig mobility group proteins. To map potential transcriptional activation or repression doains of the MLL protein, yeast GAL4 DNA-binding domain and MLL hybrid protein-expressing plaids were cotransfected with chioramphenicol a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
199
0
2

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(203 citation statements)
references
References 30 publications
2
199
0
2
Order By: Relevance
“…Using GAL4-MLL chimeras, it was shown that this region of the MLL protein contains a transcriptional activation domain [Zeleznik-Le et al, 1994]. This activation domain binds to the CREB-binding protein (CBP), a known regulator of gene expression [Ernst et al, 2001].…”
Section: Many Pieces Of the Puzzlementioning
confidence: 99%
See 1 more Smart Citation
“…Using GAL4-MLL chimeras, it was shown that this region of the MLL protein contains a transcriptional activation domain [Zeleznik-Le et al, 1994]. This activation domain binds to the CREB-binding protein (CBP), a known regulator of gene expression [Ernst et al, 2001].…”
Section: Many Pieces Of the Puzzlementioning
confidence: 99%
“…MLL contains three AT-hook motifs which have DNA binding activity, specific for AT-rich DNA [Zeleznik-Le et al, 1994]. These domains do not recognize a specific sequence but rather a structure of cruciform or bent DNA.…”
Section: Many Pieces Of the Puzzlementioning
confidence: 99%
“…Within the fMll`domain 3', we were also able to identify smaller blocks of higher identity (Figure 4). One of these, Block 5 (Figures 3 and 4), overlaps with the minimal transactivation domain (MTAD) identi®ed in vitro (Zeleznik-Le et al, 1994;Prasad et al, 1995). Two small motifs of 7 amino acids located at the carboxy-terminal end of the region encoded by exon 25a (Block 4a: QVDGADD) and at the amino-terminal end of exon 25b (Block 4b: QLDGVDD) in fMll are 100% identical to those in MLL and Mll (Figures 3 and 4).…”
Section: Comparison Of Mll/trx Proteinsmentioning
confidence: 92%
“…In the remaining exon junctions, identi®cation of appropriate splice junctions and similarity with the human protein and gene structure were utilised to predict the exon positions. b Domains are discussed in the text, b1, b2 etc refer to Block 1, Block 2 etc.`repressor' refers to the region described as a transcriptional repressor segment (Zeleznik-Le et al, 1994;Prasad et al, 1995). All other abbreviations are as in Figure 3.…”
Section: Genomic Structure Of Fmllmentioning
confidence: 99%
“…Three AT-hook DNA-binding domains near the amino terminus also are found in the high-mobility group proteins HMG-I(Y) (15). MLL contains a region of homology to mammalian DNA methyltransferases, transcriptional activation and repression domains, and a cysteine-rich region that forms three C4HC3 zinc fingers [plant homeodomain (PHD) or leukemia-associated-protein domains] (16)(17)(18)(19)(20)(21). The PHD domain and the SET [Su(var)3-9 enhancer of zeste, and trithorax] domain at the carboxyl terminus are the regions most conserved with the Drosophila trithorax (trx) protein.…”
mentioning
confidence: 99%